Strategic Technology Management Framework for Educational Institutions with Limited Resources: A Case Study of a Local College in the Philippines - Danilo C. Sabado (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In an era of rapid technological advancement, educational institutions face the challenge of effectively integrating technology to enhance teaching, learning, and administrative processes. This research aims to propose a comprehensive technology management framework tailored for local colleges in the Philippines that operate under constraints of limited budgets and resources. The framework addresses the critical aspects of technology vision, strategic alignment, competitive advantage, customer-centric approach, and efficient resource utilization. The first section delves into the establishment of a clear technology vision and mission, aligning them with the institution’s management information systems (MIS), identifying competitive advantages, and formulating guiding principles that underscore technology utilization. Understanding the institution’s customer base, defining the service portfolio, and assessing key metrics through providing valuable insights into current standing. Furthermore, a SWOT analysis identifies internal strengths and weaknesses along with external opportunities and threats. The subsequent section outlines the institution’s strategic trajectory. It defines strategic initiatives for technology integration, fostering a culture of effective communication, and establishing governance initiatives to ensure the alignment of technology decisions with institutional goals. Operational initiatives are highlighted to emphasize the importance of translating strategies into tangible actions. The final section illustrates the practical implementation of the framework. It emphasizes the connection between the institution’s overall strategy and specific technology initiatives, creating a roadmap for seamless execution. The plan implementation phase outlines the steps, responsibilities, and timelines required to achieve the outlined goals. By addressing the unique challenges faced by local colleges in the Philippines with limited resources, this proposed technology management framework provides a structured approach to capitalize on available opportunities while mitigating challenges. Through the integration of technology into various aspects of education and administration, these institutions can enhance their competitiveness, foster innovation, and provide a superior educational experience to students and stakeholders alike. This research contributes to the broader discussion of technology management in educational contexts and offers practical insights for institutions worldwide facing similar resource constraints.